Development of Novel Tavapadon Analogs as Dual-targeted Partial Agonists Based on the Dopamine D1/D5 Receptors - Fan Shi; Jian Jia; Zhijing Hu; Yini Yang; Peng Xie; Zehong Wan; Guan Wang (Pharmaceutical Fronts)
Tavapadon is a potent, selective G protein-biased partial agonist for the dopamine D1/D5 receptors, with positive experimental results in phase 3 trials for the treatment of Parkinson's disease (PD). This study aims to study the structure–activity relationship (SAR) of tavapadon to discover novel compounds with improved binding activity to D1/D5 receptors. In this work, a series of tavapadon derivatives were designed and synthesized based on the pharmacophores of tavapadon. Their binding activity to D1/D5 receptors was evaluated by determining in vitro median effect concentration (EC50). The binding mode was predicted by molecular docking. Our data showed that among those compounds, III-1 exhibited a similar binding pose to tavapadon at D1 dopamine receptors and demonstrated nanomolar potency for both D1 and D5 receptors. Compound III-1 is a potent partial agonist for the D1/D5 receptors, and may be a potent alternative to tavapadon for the treatment of PD in further study.